2019
DOI: 10.56093/ijas.v89i4.88841
|View full text |Cite
|
Sign up to set email alerts
|

Foliar and soil N fertilization as a function of cropping behaviour of Royal Delicious apple (Malus domestica)

Abstract: The key factor to obtain good yield and high fruit quality in apple (Malus domestica Borkh.) production is tree fertilization. The present study was planned with the objective to investigate the effect of soil applied N sources through foliar Urea sprays on morphometric growth traits, yield and fruit quality of apple cv. Royal Delicious. The trial was carried out on 28-year old trees raised on Crab apple Malus sylvestris (L.) Mill rootstock. Soil application of N sources, viz. Urea, calcium nitrate (CN), N:P:K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Given chemical fertilizers can quickly provide available nutrients to apples, they have been widely used as the main nutrient source in apple orchards in China [33]. Recently, accumulated evidence has revealed that organic fertilizer substitution has great promoting effects on crop yield and fruit quality, because additions of organic fertilizers can supply organic matter and a variety of nutrients into the soil [34][35][36]. Consistently, in our present study, we found that the organic substitution improved apple quality indicators, including TS and Vc contents, sugar/acid ratio, and fruit hardness.…”
Section: Organic Substitution Increased the Yield Of Large-size Fruit...mentioning
confidence: 99%
“…Given chemical fertilizers can quickly provide available nutrients to apples, they have been widely used as the main nutrient source in apple orchards in China [33]. Recently, accumulated evidence has revealed that organic fertilizer substitution has great promoting effects on crop yield and fruit quality, because additions of organic fertilizers can supply organic matter and a variety of nutrients into the soil [34][35][36]. Consistently, in our present study, we found that the organic substitution improved apple quality indicators, including TS and Vc contents, sugar/acid ratio, and fruit hardness.…”
Section: Organic Substitution Increased the Yield Of Large-size Fruit...mentioning
confidence: 99%